Regulasi Komunikasi Interpersonal Dalam Demokratisasi Pendidikan Indonesia (Studi Deskriptif Restorasi Dunia Pendidikan Di Indonesia Dalam Perspektif Henry Giroux) - Erwin Setyawan; Yohanes Probo Dwi Sasongko (Universitas Bina Sarana Informatika, 2021)
Efforts to continue to sustain the education process amidst the current pandemic, cannot be denied that it is becoming a global problem in the world and in Indonesia. Changing the learning mechanism, the high dropout rate for students. The lack of good communication within the central government in applying the rules of learning in higher education institutions has attracted a lot of reactions from a number of parties. Today's education is focused on seeking profit only and teaching patterns that make students the object. This restraint occurs both inside the classroom and outside the classroom. Children who are creative and diligent in asking questions will be labeled as rebellious because they are considered brave enough to fight against the teacher. Henry Giroux, as one of the leading educational observers, stated that children should be given the freedom to explore themselves. Students are given space and opportunities to learn for every productive age. Education should aim at advancing children's thinking and giving them opportunities to be creative. This article intends to try to provide an overview of the education needed for the future of Indonesian students. This study uses a qualitative method, with a comprehensive descriptive approach regarding policy regulations and interpersonal communication efforts by the government and related agencies. How to determine policies that are applicable and can be applied by the Indonesian people in pursuing education. What steps and actions should be applied in addressing and beyond the world of homeland education. This is what will be reviewed and presented in several books and journals on education. with the hope that one day education can become a teaching method that provides life and supports the future of our next generation.